Full-Term Delivery and Complete Lung Recovery following VV ECMO Support Midpregnancy in a Patient with COVID-19 ARDS - Shelley Leong; Guillermo Moreno; Mohamed Fayed; Crystal Ives Tallman (Case Reports in Critical Care)
Pregnant women are especially vulnerable to coronavirus disease 2019 (COVID-19). We present a twin pregnancy case with acute respiratory distress syndrome following COVID-19 infection at 19 weeks. The patient’s ARDS was successfully managed with veno-venous extracorporeal membrane oxygenation (VV ECMO). She recovered completely and delivered healthy twins.